Design, synthesis, and computational validation of novel compounds selectively targeting HER2-expressing breast cancer. Issue 24 (15th December 2020) - Elseginy, Samia A.; Hamdy, Rania; Menon, Varsha; Almehdi, Ahmed M.; El-Awady, Raafat; Soliman, Sameh S.M.
Graphical abstract: Highlights: New compounds with specific targeting to HER2 receptor are designed. The compounds target only the HER2 + cells. Computational modeling proved the specificity of the developed structures. Abstract: Human epidermal growth factor receptor (HER) is a family of multidomain proteins that plays important role in the regulation of several biological functions. HER2 is a member of HER that is highly presented in breast cancer cells. Here, we designed and synthesized a series of diaryl urea/thiourea compounds. The compounds were tested on HER2 + breast cancer cells including MCF-7 and SkBr3, compared to HER2 - breast cancer cells including MDA-MB-231 and BT-549. Only compounds 12–14 at 10 µM showed selective anti-proliferative activity against MCF-7 and SkBr3 by 65–79%. Compounds 12–14 showed >80% inhibition of the intracellular kinase domain of HER2. The results obtained indicated that compounds 12–14 are selectively targeting HER2 + cells. The IC50 of compound 13 against MCF-7 and SkBR3 were 1.3 ± 0.009 and 0.73 ± 0.03 µM, respectively. Molecular docking and MD simulations (50 ns) were carried out, and their binding free energies were calculated. Compounds 12–14 formed strong hydrogen bond and pi–pi stacking interactions with the key residues Thr862 and Phe864. 3DQSAR model confirmed the role of 3-bromo substituent of pyridine ring and 4-chloro substituent of phenyl ring in the activity of the compounds. In conclusion, novel compounds, particularly 13 were developed selectively against HER2-expressing/overexpressing breast cancer cells including MCF7 and SkBr3.